Exploring the Potential of AI-Driven Personalized Learning and Cognitive Interventions for ADHD Management in Indian Children and Adolescents: A Focus on Early Intervention - Meher Malik (International Journal of Brain Sciences, 2025)
Attention Deficit Hyperactivity Disorder (ADHD) is a prevalent neurodevelopmental condition that significantly impairs attention, executive functioning, and behavioural regulation in children and adolescents. In India, the management of ADHD is particularly challenging due to low public awareness, social stigma, and a critical shortage of specialized mental health services, especially in rural areas. These systemic barriers often lead to delayed diagnoses and limited access to consistent care. However, with the rapid advancement of artificial intelligence (AI), new opportunities are emerging for delivering personalized learning experiences and cognitive interventions tailored to the unique needs of neurodiverse populations. This paper explores the potential of AI-driven tools in addressing ADHD among Indian children and adolescents, emphasizing earl intervention as a crucial step toward improving long-term academic, emotional, and social outcomes. By conducting a comprehensive secondary analysis of over 40 empirical studies and reviews, the research evaluates the efficacy, accessibility, cultural adaptability, and ethical implications of AI-based interventions. The findings demonstrate substantial improvements in attention span, behavioural self-regulation, and classroom engagement through adaptive learning systems, gamified cognitive tasks, and virtual coaching platforms. Despite these encouraging outcomes, significant concerns persist, including algorithmic bias, data privacy risks, and the widening digital divide between urban and rural populations. This study underscores the need for culturally sensitive AI models, robust ethical frameworks, and sustained public-private collaboration. Through interdisciplinary efforts and infrastructure development, AI holds the potential to become a transformative force in making ADHD management more accessible, inclusive, and effective across India’s diverse educational and healthcare landscape.
Keywords: ADHD; Cognitive Interventions; Digital Accessibility; Early Intervention; Personalized learning; artificial intelligence